Does Venue Type Matter for HIV-Related Risk Behavior in Urban Adolescent and Young Adult Men Who Have Sex With Men?. Issue 8 (November 2019) - Arrington-Sanders, Renata; Fields, Errol; Greenberg, Lauren; Henry-Reid, Lisa; Stines Pehoua, Stephanie; Korelitz, James; Kapogiannis, Bill; Ellen, Jonathan; Boyer, Cherrie B.
Venue-based strategies offer effective means of targeting men who have sex with men. Few studies have sought to focus on where younger men congregate and understand risk behaviors that may occur at lower (i.e., community centers) versus higher risk venues. Data from 1, 311 young men who have sex with men (YMSM) aged 12- to 24-years-old recruited from publicly accessible venues was used to examine the association between venue type (bar/club, community center, mixed [adjacent to bar/club, including parking lot/alley]) and HIV-related risk factors. YMSM recruited from community venues were more likely than those from bars/clubs to report more partners in last year, receive money in exchange for sex, and to be tested for HIV in prior 6 months, whereas YMSM from mixed-use venues were more likely to have ever received money in exchange for sex, and injected drugs. Community and mixed venues may be key access points for YMSM.